The Level of social Emotional Competence According to the (CASEL) Model among a Sample of Second Cycle Students (Afield study in the Schools of Lattakia city) - حسون نعمه; ريما سعدي (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The research aims to identify the level of social emotional competence among a sample of Students in the second cycle in the schools of the city of Lattakia from (from the seventh and eighth grades, in addition to Knowing differences in level of These Competence According to set of variables (gender, academic achievement, grade level). The research sample included (156) male and female Students of the schools of the city of Lattakia. For the research tools, the Social Emotional Competence scale was applied (Zhou & Je, 2012), And the Researcher studied Its Psychometric characteristics. The Results showed that the level social emotional competence among the students was average, as it reached the value of the arithmetic mean (3.23), and relative importance reached (64.6%), And the degree of the arithmetic mean of the five dimensions converged, self –awareness was first place, relationship management in the second place, then responsible decision making comes in the third place, then social-awareness in the fourth place, and Relationship comes in the fifth and final place. the Results showed that there were no statistically significant differences in the level of social emotional learning competence according to the (gender, academic achievement variable), while differences Statistical appeared spreads according to the variable of the grade level and in Favor, of the seventh grade students.